Cognitive impairment and its relation to predominant polarity, number of episodes and illness duration in patients with euthymic bipolar affective disorder (BAD) - Ratnatunga, S.S.; Kulathilake, I.C.; Kokila Medhavini, K.; Dayabandara, M.; Rajapakse, I.; Hanwella, R.; De Silva, V. (Elsevier, 2017)
Introduction: Previous optimistic assumptions about the prognosis of BAD based on the control of mood symptoms is now challenged as majority of patients continue to have cognitive deficits during the euthymic phase. Objectives: To describe cognitive impairment in euthymic BAD and study the association with clinical characteristics. Aims: Identify the prevalence and severity of cognitive impairment (CI); to correlate CI with the first episode, illness duration, number of episodes and predominant polarity. Methods: Patients attending the psychiatry clinic of the National Hospital of Sri Lanka diagnosed with BAD in the remission phase were recruited. An interviewer-administered questionnaire and Montreal Cognitive Assessment test was used to ascertain clinical characteristics and cognitive functions respectively. Scores of 18–26 described as mild, 10–17 moderate and < 10 as severe cognitive impairment. Results: Total sample size was 58. Mean age = 48.84 (SD12.5). Fifty-five percent were females. Mean duration of illness was 179.7 months (SD128.5). A mean of 6 episodes were experienced during the course of illness (min = 1, max = 18); 58.6% had depression, 37.9% had manic and 3.4% had mixed as their first episode. The predominant polarity was depressive in 65.5%. No cognitive impairment – 8.6%, mild – 63.8%, moderate – 27.6% and none with severe. There was a significant association between the presence of cognitive impairment and the predominant polarity being depressive (r = 10.886, df = 4, P = 0.028). No significant association was found between illness duration, number of episodes or the type of first episode. Conclusions: Patients with a predominant depressive polarity are more likely to experience cognitive impairment. Cognitive impairment had no association with illness duration, type of episode or number of episodes.
Keywords: bipolar affective disorder